Numerical study on phase change of water flowing across two heated rotating circular cylinders in tandem arrangement. (December 2016) - Dhar, BK; Mahapatra, SK; Maharana, SK; Sarkar, A; Sahoo, SS
The problems of fluid flow and heat transfer phenomena over an array of cylinders are quite prominent in fluid dynamics and industry applications. The current work focuses on fluid flow and heat transfer analysis over two heated rotating cylinders arranged in tandem. The flow of water over heated cylinders faces a phenomenon of phase change from liquid (water) to vapor phase (steam). The mechanism of this phase change is studied through a numerical simulation supplemented with verification of the code and validation. The problem is simulated when flows from two cylinders in a tandem arrangement become interacting and non-interacting. The Eulerian model is used during simulation to comprehend the multiphase phenomena. The volume fractions of both the phases such as water and vapor and heat transfer coefficients of both the cylinders have been computed and presented as findings of the problem. The mass and heat transfer mechanism is unidirectional from one phase to the other phase. The vapor fraction of each phase is to be observed and compared when three different rotations are given to the two cylinders immersed in a turbulent flow of water.